PENGARUH UANG SAKU, GAYA HIDUP, DAN PENGGUNAAN FINANCIAL TECHNOLOGY TERHADAP PERILAKU MENABUNG MAHASISWA PENDIDIKAN EKONOMI - Fitri Nur Afni; Rendra Gumilar; Yoni Hermawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to empirically analyze the impact of pocket money, lifestyle, and the use of financial technology on the saving behavior of Economic Education students of the Faculty of Teacher Training and Education, Siliwangi University batch 2021-2022. The research method used is the survey method. The population in this study were all Economic Education students in the 2021 and 2022 batches, with the sampling technique using proportionate stratified random sampling. Data collection was carried out using a questionnaire, and data analysis using multiple linear regression. The results showed that: 1) Pocket money has a positive and significant effect on student saving behavior with a significance value of 0.000 <0.05. 2) Lifestyle has a positive and significant effect on student saving behavior with a significance value of 0.000 <0.05. 3) The use of financial technology has a positive and significant effect on student saving behavior with a significance value of 0.013 <0.05. 4) Pocket money, lifestyle, and the use of financial technology simultaneously have a positive and significant effect on student saving behavior, as evidenced by the Fhitung value of 66.277> Ftabel 2.67 with a significance value of 0.000 <0.05.